Cost of doing a research: comparing participatory and conventional silviculture research in Nepal - Acharya, K; Goutam, K (2005)
Participatory forestry known as community forestry is now widely adopted as a means to develop sustainable rural livelihoods. It is focused on forest management and improved access to multiple forest products. The diverse needs of communities living in different climatic and ecological zones and under different socio-economic conditions have imposed a pattern of a multitude of localized forestry research studies in Nepal. The increasing demand for forestry products can only be met through the development, adoption and implementation of innovative technologies in managing forest resources. Thus, forestry research in Nepal has the responsibility for providing useful and updated information for the management of declining forest resources both to local users and to centrally located policy makers. The traditional research has largely failed to provide this information and respond to the challenges of sustainable forestry development in Nepal and has largely been constrained with the lack of financial resources. The Department of Forest Research and Survey under the Ministry of Forest and Soil Conservation has initiated participatory research approach in mid 90's with a view to develop methodologies suitable to address multiple demands of people living in heterogeneous conditions. The vision is of an effective and powerful partnership of civil and government stakeholders agreeing a research programme, providing resources, executing and evaluating it continuously and effectively. The paper presents the costs evaluation of two research sites on forest silviculture and management for a period of 6 years from two research sites. The first study is a conventional silviculture research established by the department seeking appropriate management options for Sal (Shorea robusta) forest. Similarly, the focus of the second plot is to explore the management potential of Sal forests in the mid hills of Nepal. The second research is a participatory carried out in partnerships with a forest user group in a community forests. The paper analyses nature of the costs, magnitude, structure, and temporal behaviors of the costs at various stages of research planning and management process. In addition, nature and share of these costs among the department and the participant forest users group is compared. There is considerable variation in the structure and magnitude of the costs in participatory and conventional research. The result clearly provides evidences that participatory research is significantly cheaper compared to conventional forestry research. The research establishment, protection and maintenance costs are drastically lower in participatory research. The information provides evidences for research manager to justify its existence by providing the results and answers required by its clients in the fight against poverty, forest degradation and environmental deterioration. The cost evaluation and adoption of participatory research can justify the use of scarce resources and demonstrate researchers ability to provide the information needed by clients and make the research institution effective and functional.